2019
DOI: 10.3233/jad-180820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microglial Cytokines on Alzheimer’s Disease-Related Phenomena

Abstract: Recent association studies indicate several genes highly expressed by microglia influence Alzheimer’s disease (AD) risk, which suggests microglial function contributes to this disease. Here, we evaluated how one component of microglial function, cytokine release, affects AD-related phenomena. First, we used a 3-hour lipopolysaccharide (LPS) treatment to activate mouse BV2 microglial cells. Next, we removed the LPS-containing medium, added LPS-free medium, and after 6 hours collected the medium conditioned by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…Previous reports on LD aggregation in neurons are scarce. Ji et al reported a decrease in LD aggregation in SH-SY5Y cells following the incubation with BV2 cell line supernatant [29], which is inconsistent with our ndings. We speculate that this discrepancy may stem from variations in experimental conditions, culture systems, such as the source and passage of cell lines, or differences in LPS processing method.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports on LD aggregation in neurons are scarce. Ji et al reported a decrease in LD aggregation in SH-SY5Y cells following the incubation with BV2 cell line supernatant [29], which is inconsistent with our ndings. We speculate that this discrepancy may stem from variations in experimental conditions, culture systems, such as the source and passage of cell lines, or differences in LPS processing method.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the resting-balanced microglia phenotype (M0) with ramified appearance is the main type of microglia residing in the parenchyma of the healthy brain. Depending on the type of the exposed environment and the identified stimulus, M0 implies different phenotypes, whether M1/TH1 or M2/TH2 phenotype ( Guedes et al, 2018 ; Ji et al, 2019 ; Leng and Edison, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar immune responses regarding most of those cytokines were also found in the CM of LPS induced BV-2 cells by the previous studies (Li et. al.,2016;Ji et. al., 2019).…”
Section: Discussionmentioning
confidence: 99%